The effect of silage quality on gross energy losses - Sakhawat, Irfan (SLU/Dept. of Animal Nutrition and Management (until 231231), 2011)
Silage is a feed for ruminants resulting in the preservation of fresh forage crops by acidification, which is achieved under anaerobic environment. The process of ensiling is mainly depends upon the chemical and microbial composition of forage. During the fermentation process, changes in chemical composition of forage occur mainly due to bacterial activities. These changes are always accompanied with losses commonly expressed as DM losses. Another way to express these losses is in form of gross energy losses. The aim of the study was to investigate the effect of quality of silage fermentation influenced by silage additive application on the gross energy value of silages after the fermentation process and after aerobic stability test. Clover-grass mixture in 22 % DM treated with silage additive at the rate 1L, 2L, 3L and 5 L per ton fresh forage was compared with untreated control. Forage was ensiled in 1.7 glass jars with water lock for 90 days. Chemical and microbiological analyses were performed to determine fermentation quality of silages. In addition, silages were weighed to determine DM losses as well as aerobic stability test was performed on silages. The gross energy was analyzed by bomb calorimetric method. The pH of control silages was significantly higher (P<0.001) than the additive treated silages. The production of propionic acid (P<0.001), butyric acid (P<0.001), 2,3-butanediol (P<0.001) and ethanol (P<0.001) was significantly reduced in all additive treated silages in comparison with the control silage. The concentration of lactic acid (P<0.001) and acetic acid (P<0.001) was higher in additive treated silages than in control. The concentration of ammonia-N was found lower (P<0.04) in S2 and S3 silages in comparison with the rest of silages. Clostridia spore count was significantly reduced (P<0.001) in all additive treated silages in comparison with the control silage. The DM losses in control silages were found to be higher (P<0.001) during the whole storage time in contrast with treated silages. No differences in aerobic stability were found between additive treated and control silages. There were no statistical differences between gross energy of all silages and gross energy of fresh forage in both after fermentation and after the stability test. Energy losses expressed in % of initial energy concentration in the silo showed no significant variations among both silages, after fermentation (P=0.5) and after the stability test (P=0.2). The improved the silage fermentation by the application of silage additives was reflected in reduced DM losses. However, the improvement in silage fermentation had no effect on energy losses formation in silages.